2022
DOI: 10.1371/journal.pone.0276582
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of hepatitis C virus using recombinase polymerase amplification

Abstract: Over 71 million people are infected with hepatitis C virus (HCV) worldwide, and approximately 400,000 global deaths result from complications of untreated chronic HCV. Pan-genomic direct-acting antivirals (DAAs) have recently become widely available and feature high cure rates in less than 12 weeks of treatment. The rollout of DAAs is reliant on diagnostic tests for HCV RNA to identify eligible patients with viremic HCV infections. Current PCR-based HCV RNA assays are restricted to well-resourced central labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…27 Chia et al applied an assay based on RT-recombinase polymerase amplification and identified an LoD of 25 copies per test. 28 It was obvious that the novel assay in this study was more sensitive than the approaches previously reported.…”
Section: Discussionmentioning
confidence: 78%
“…27 Chia et al applied an assay based on RT-recombinase polymerase amplification and identified an LoD of 25 copies per test. 28 It was obvious that the novel assay in this study was more sensitive than the approaches previously reported.…”
Section: Discussionmentioning
confidence: 78%
“…The optimal probe-primer combination from two probes and 10 primers was selected to amplify the ORF2 gene, which were used as the target sequence because they were reported to be highly conserved in several previously developed methods based on nucleic acid ampli cation, but a few sequence variations still appeared in the ORF2 genes of GoAstV-2 strains. The RPA assay was reported to be able to tolerate 5-9 target mismatches with little in uence on the results of the assay [31,32]. The probe-primer set used in this study had a strong uorescence signal and no cross-reaction with other related pathogens, demonstrating good ampli cation e ciency and high speci city of the assay.…”
Section: Discussionmentioning
confidence: 85%
“…Enzyme-assisted isothermal methods include nucleic acid sequence amplication (NASBA), 11,12 loop-mediated isothermal amplication (LAMP), [13][14][15] rolling circle amplication (RCA), 16,17 and recombinase polymerase amplication (RPA). 18,19 However, dependence on enzyme catalysis introduces supply, cost, and technical hurdles that need to be addressed for decentralized adoption. Enzyme-free techniques present a promising solution, instead utilizing the inherent self-assembly of nucleic acidssuch as Watson-Crick base pairing and nucleoside modicationsto construct nanostructures in a bottom-up approach.…”
Section: Conventional Diagnostic Approaches For Hcvmentioning
confidence: 99%